Avaliação de antioxidantes comerciais e sintético na estabilidade de ésteres derivados do ácido oleico e ricinoleico - Freitas, Daniele Barbosa (2024)
Lubricants play a crucial role in reducing friction and wear between machine parts and transmission systems. With growing environmental and economic concerns, there is a preference for lubricants formulated from renewable oil sources, known for their biodegradability and lower toxicity. To enhance the properties of oils, regardless of their origin, the inclusion of additives becomes essential. These additives aim to optimize the oil's performance. In this context, the present study aimed to evaluate the antioxidant potential of an additive derived from cardanol (PCDN), the main component of cashew nutshell liquid, as well as two other commercial additives, PDA (di-sec-butyl-p-phenylenediamine) and tritolyl phosphate, when applied to bioesters. Confirmation of the synthesis was carried out through characterization techniques including FTIR, NMR, and TGA. The antioxidant potential of the obtained compound was subsequently compared to the other two additives through oxidation tests using the Rancimat method. The results indicated that the synthesized additive increased the oxidative stability time (OST) of bioesters by approximately three times, going from 4.25 to 18.30 hours and 25.64 to 94.61 hours, surpassing the performance of the phosphorus-based commercial additive, which showed no significant changes in OST, going from 4.25 to 4.75 hours and 25.64 to 26.10 hours. The aminated additive achieved the best value, exceeding 100 hours for both bioesters. Regarding thermal stability, there was an increase in the onset temperature of degradation (Tonset) for one of the analyzed esters, going from 155ºC to 205ºC with the addition of 1% PCDN and reaching 300ºC with 1% PDA. These results demonstrate that both additives contribute to improving the thermal stability of the oil. Therefore, it can be inferred that the cardanol-derived additive emerges as a promising alternative, given its demonstrated effectiveness and sustainable origin.